Training on Making Biopesticide Made from Daun Belimbing Wuluh at the Women's Farming Group “Nanas Madu” in Buket Meutuah Village, Langsa City - Boy Riza Juanda; Iswahyudi; Iwan Saputra (Fakultas Pertanian, Universitas Samudra, 2023)
The majority of farmers in Indonesia still use chemical pesticides to treat pests and diseases in the commodities they grow. One of the plants that can be used as an environmentally friendly alternative to biopesticides is starfruit leaves. The large availability and ease of obtaining starfruit leaves, especially in Aceh in general and in Langsa City in particular, makes it potential to be used as a biopesticide which can be used by farmers in Langsa City, especially vegetable farmers. The farmer group that is a partner in this service activity is the